¿Brujas o ángeles? algunos ejemplos de misoginia en el mundo clásico - Real Torres, Carolina (1997)
The Classical Antiquity is a rich period which offers many cases of misoginy. This paper is an attempt to draw a reasonable explanation of some features of the behaviour of women in society. It also gives an account of the various kinds of restrictions imposed on them.
Keywords: Misoginia; Mujeres